2020
DOI: 10.1080/08920753.2020.1802198
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Fishery-Based Livelihoods to Extreme Events: Local Perceptions of Damages from Hurricane Irma and Tropical Storm Alberto in Yaguajay, Central Cuba

Abstract: Hurricanes can cause extensive long-term damage to small-scale fisheries. Yet, information is scarce on how communities are locally impacted by extreme events in the Caribbean and in other parts of the world. Focusing on an artisanal fishery in Yaguajay, Sancti Spiritus, Cuba, this article explores how artisanal fishers have perceived and responded to the different damages brought about by Hurricane Irma in September 2017 and the inundations associated with Storm Alberto in May 2018. Combining discussions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…These factors may have created conditions for them to suffer greater damage when the storms pass. According to Ramenzoni et al (2020), the impacts of climatic events in the fisheries sector are varied, including changes in ecological conditions, acceleration of coastal zone degradation through soil entrainment, vegetation degradation. Our results agree with those reported by McConney et al (2009), who identified the effects of climate change on smallscale fisheries in the eastern Caribbean where they indicated a negative biological response from fish when ocean temperatures changed due to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may have created conditions for them to suffer greater damage when the storms pass. According to Ramenzoni et al (2020), the impacts of climatic events in the fisheries sector are varied, including changes in ecological conditions, acceleration of coastal zone degradation through soil entrainment, vegetation degradation. Our results agree with those reported by McConney et al (2009), who identified the effects of climate change on smallscale fisheries in the eastern Caribbean where they indicated a negative biological response from fish when ocean temperatures changed due to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…This research included several variables and risk-perception questions to generate a socioenvironmental vulnerability index and an extended questionnaire for community perception analysis, a technique universally used [35][36][37]. Recently, researchers have pointed out that climate-change impacts are associated with social vulnerability; thus, impact assessments must also be viewed through a social lens [29,38].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, inhabitants can underestimate the potential negative effects of this factor (data georeferenced in Figure 1). These georeferenced survey results and flooding hazard maps showed sensible information for prevention of losses and are especially useful as a base to build dynamic models that perform process simulation and forecast in future events, especially for sites that have suffered a loss of biodiversity, as is the case for Los Cabos because of its urban development [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in extreme weather events or bad weather days, for example, has the potential to affect fishers' infrastructure, including boats and gear, disrupt fishing effort, and cause physical harm to the fishers themselves (Daw et al, 2009;Sumaila and Cheung, 2010;Sainsbury et al, 2018;Heck et al, 2021). Small-scale fishers (SSF) in particular, are highly susceptible to changes in weather and climate conditions, due to their high dependency on resources, exposure to the elements, and sensitivity to impacts (Huber and Gulledge, 2011;Onyango et al, 2012;Limuwa et al, 2018;Freduah et al, 2019;Thoya and Daw, 2019;Karlsson and Mclean, 2020;Ramenzoni et al, 2020;Turner et al, 2020). This is concerning given that over half of all fish caught in developing countries is produced by SSF and up to 95 percent of these landings are for local consumption (The World Bank, 2012).…”
Section: Introductionmentioning
confidence: 99%